Experimental study on the forced convection heat transfer characteristics of airflow with variable thermophysical parameters in a circular tube. (December 2022) - Zhao, Qijin; Mao, Baoquan; Zhao, Junyan; Li, Huaying; Wei, Shuguang; Bai, Xianghua; Zhang, Xinxi; Zhang, Yunyin
Abstract: The heat transfer of fluids in pipelines under conditions with variable thermophysical parameters is ubiquitous in engineering applications, but effective methods to predict the heat transfer parameters are scarce. To address this issue, an experimental method was proposed to measure the heat transfer parameters in a circular tube by considering the effect of the insufficient development of turbulence in the inlet region and a Robin boundary on the wall. The variation of the Nusselt number of the inner wall was calculated by measuring the temperature distribution of the outer wall, and a temperature-related Gnielinski correlation was developed for conditions under which the thermophysical parameters vary with the fluid temperature. The results demonstrated that the deviations between the experimental Nusselt numbers and the values predicted using the traditional Gnielinski correlation became larger and larger as the flow distance increased. The temperature-related correlation generally improved the prediction accuracy by more than 25%, and the accuracy was better with increasing inlet temperature and decreasing airflow velocity. This study provides an important empirical reference for the prediction of the convective heat transfer parameters in pipelines and related engineering applications under strong heating or cooling conditions.